A PROSPECTIVE OBSERVATIONAL CASE SERIES OF OPHTHALMIC MANIFESTATIONS AND TREATMENT MODALITY OF RHINO-OCULO-CEREBRAL MUCORMYCOSIS DURING SECOND WAVE OF COVID PANDEMIC IN A TERTIARY CARE HOSPITAL. - Behera, Prativa; Padhy, Sujata; Dash, Suchitra; Priyadarshini, Deepika (Student’s Journal of Health Research Africa, 2023)
Aim: During the second wave of the COVID-19 pandemic in India, there has been a significant increase in the prevalence of COVID-19-associated rhino-orbital-cerebral mucormycosis (ROCM). In this investigation, the primary objective was to ascertain the ocular manifestations of risk factors encompassing comorbidities and pharmacological interventions employed in the management of COVID-19. Methodology: This study presents a prospective, observational case series examining patients diagnosed with COVID-19-associated rhino-orbital-cerebral mucormycosis (ROCM) who exhibited ocular manifestations. The patients included were seen at the eye outpatient department, admitted to the ear, nose, and throat department, and received treatment for COVID-19 at a designated COVID hospital. The study was conducted for a duration of three months, from 1st May 2021 to 30th August 2021. Results: The majority of cases developed ROCM symptoms between day 10 and day 15 after COVID-19 diagnosis, with 56% developing within 14 days and 44% developing beyond 14 days. Orbital involvement, with stage 3c, comprises the majority (27%) of the total. 73% received intravenous amphotericin B, 56% underwent pa: ranasal sinus (PNS) debridement/ functional endoscopic sinus surgery (FESS), 3% received both orbital exenteration and PNS/ FESS debridement, and 15% underwent orbital exenteration. Intraorbital amphotericin B injections were administered in 22% of cases. The final follow-up revealed a 14% mortality rate. Conclusion: Diabetes mellitus and corticosteroids are the most significant risk factors for COVID-19-associated ROCM development. COVID-19 patients must be followed even after recovery. A successful outcome requires a high index of clinical suspicion, awareness of red flag signs and symptoms, speedy diagnosis, early treatment initiation with amphotericin B, orbital exenteration when indicated, and aggressive surgical debridement of the PNS. Recommendation: In the case of COVID-19 patients who are suffering from diabetes mellitus and are treated with corticosteroids, physicians should be vigilant and monitor patients carefully for the occurrence of rhino-orbital-cerebral mucormycosis.